The Effectiveness of Law Application against the Crime of Narcotics Abuse of Category I According to Law Number 35 of 2019 concerning Narcotics (At BNNP Bengkulu) (JURNAL HUKUM SEHASEN, 2020)
Narcotics are substances or drugs derived from plants or non-plants, both synthetic and semisynthetic, which can cause a decrease or change in consciousness, loss of taste, reduce to eliminate pain, and can cause dependence, which are divided into groups as attached in Law Number 35 of 2009 concerning Narcotics. Abuse is a person who uses narcotics without rights or against the law. The National Narcotics Agency of Bengkulu Province is a vertical Government Institution located under and responsible to the National Narcotics Agency which is an institution that aims to carry out the Drug Prevention and Illicit Trafficking Program (P4GN) with various activities through the field of Prevention and Community Empowerment. In hindsight, the problem in this research is the application of law in handling the abuse of narcotics crime class I at BNNP Bengkulu. Theories of the causes of crime as for several theories about the causes of crime, this type of research is an empirical research. Narcotics abuse of class I in the National Narcotics Agency of Bengkulu Province. Drug Abuse and Illicit Trafficking (P4GN) with various activities through the field of prevention and community empowerment in the field of Rehabilitation and the Field of Implementation of strategic plans and work plans in the field of opposition and eradication and illicit trafficking of narcotics, psychotropics, precursors and addictive substances other than addictive substances for tobacco and alcohol which was later called P4GN in the Bengkulu Province Region. Implementation of technical policies in the field of community empowerment, rehabilitation and eradication in the Bengkulu Province Region.